Преобразование дробей .

Сложные .








1.    \(\dfrac{x^2+2xa+a^2}{a-x}:\dfrac{x+a}{2x-2a} \)


  

\( -2x-2a \)

\(\dfrac{x^2+2xa+a^2}{a-x}:\dfrac{x+a}{2x-2a}= \dfrac{(x+a)^2}{a-x} \cdot \dfrac{2x-2a}{x+a}= \)


\(= -\dfrac{(x+a)^2}{x-a}\cdot \dfrac{2(x-a)}{x+a}=-\dfrac{x+a}{1}\cdot \dfrac {2}{1}=-2x-2a \)


ПОЗЖЕ



2.   \(\dfrac{9a^2+30a+25}{x-a}:\dfrac{5+3a}{a-x} \)


  

\( -3a-5 \)

\( \dfrac{9a^2+30a+25}{x-a}:\dfrac{5+3a}{a-x}=\dfrac{(3a+5)^2}{x-a} \cdot \dfrac{a-x}{5+3a}= \)


\(= -\dfrac{(3a+5)^2}{a-x}\cdot \dfrac{a-x}{3a+5}= -\dfrac{3a+5}{1}\cdot \dfrac{1}{1}=-3a-5 \)


ПОЗЖЕ



3.   \( (\dfrac{4a^2}{4a^2+4a+1}+\dfrac{2}{2a+1}):\dfrac{2+4a+4a^2}{(2a+1)^2} \)


  

\( 1 \)

Выполним по действиям:
\( 1)\;\;\;\;\;\;\; \dfrac{4a^2}{4a^2+4a+1}+\dfrac{2}{2a+1}=\dfrac{4a^2}{(2a+1)^2}+ \dfrac{\;\;\;\;2^{\;\;(2a+1}}{2a+1}= \dfrac{4a^2+4a+2}{(2a+1)^2} \)



\( 2)\;\;\;\;\; \dfrac{4a^2+4a+2}{(2a+1)^2}:\dfrac{2+4a+4a^2}{(2a+1)^2}=\dfrac{4a^2+4a+2}{(2a+1)^2} \cdot \dfrac{(2a+1)^2}{2+4a+4a^2}=1 \)


ПОЗЖЕ




4.    \( (1-\dfrac{4x^2+81}{36x}): (\dfrac{1}{2x}-\dfrac{1}{9})-x\)


  

\( - 4,5 \)

Выполним по действиям:

\( 1)\;\;\;\;\; 1-\dfrac{4x^2+81}{36x}= \dfrac{\;\;\;1^{(36x}}{1}-\dfrac{4x^2+81}{36x}=\dfrac{36x-4x^2-81}{36x} \)

\( 2)\;\;\;\;\; \dfrac{1}{2x}-\dfrac{1}{9}=\dfrac{\;\;\;1^{(9}}{2x}-\dfrac{\;\;\;1^{(2x}}{9}=\dfrac{9-2x}{18x} \)


\( 3)\;\;\;\;\;\dfrac{36x-4x^2-81}{36x}:\dfrac{9-2x}{18x}=\dfrac{-4x^2+36x-81}{36x} \cdot\dfrac{18x}{9-2x}= \)


\( =\dfrac{-(4x^2-36x+81)}{36x}\cdot\dfrac{18x}{9-2x}=\dfrac{-(2x-9)^2}{36x}\cdot\dfrac{18x}{9-2x}= \)


\(= \dfrac{-(9-2x)^2}{36x}\cdot\dfrac{18x}{9-2x}= \dfrac{-(9-2x)}{36x}\cdot\dfrac{18x}{1}=\dfrac{-(9-2x)}{2} \)


\( 4)\;\;\;\;\;\dfrac{-(9-2x)}{2}-x=\dfrac{-9+2x}{2}-\dfrac{x}{1}=\dfrac{2x-9}{2}-\dfrac{\;\;x^{(2}}{1}=\dfrac{2x-9-2x}{2}= -4,5 \)



ПОЗЖЕ





5.    \( (1-\dfrac{16x^2+9}{24x}): (\dfrac{1}{4x}-\dfrac{1}{3})-2x\)


  

\( - 1,5 \)

Выполним по действиям:

\( 1)\;\;\;\;\; 1-\dfrac{16x^2+9}{24x}= \dfrac{\;\;\;1^{(24x}}{1}-\dfrac{16x^2+9}{24x}=\dfrac{24x-16x^2-9}{24x} \)

\( 2)\;\;\;\;\; \dfrac{1}{4x}-\dfrac{1}{3}=\dfrac{\;\;\;1^{(3}}{4x}-\dfrac{\;\;\;1^{(4x}}{3}=\dfrac{3-4x}{12x} \)


\( 3)\;\;\;\;\;\dfrac{24x-16x^2-9}{24x}:\dfrac{3-4x}{12x}=\dfrac{-16x^2+24x-9}{24x} \cdot\dfrac{12x}{3-4x}= \)


\( =\dfrac{-(16x^2-24x+9)}{24x}\cdot\dfrac{12x}{3-4x}=\dfrac{-(4x-3)^2}{24x}\cdot\dfrac{12x}{3-4x}= \)


\(= \dfrac{-(3-4x)^2}{24x}\cdot\dfrac{12x}{3-4x}= \dfrac{-(3-4x)}{24x}\cdot\dfrac{12x}{1}=\dfrac{-(3-4x)}{2} \)


\( 4)\;\;\;\;\;\dfrac{-(3-4x)}{2}-2x=\dfrac{-3+4x}{2}-\dfrac{2x}{1}=\dfrac{4x-3}{2}-\dfrac{\;\;2x^{(2}}{1}=\dfrac{4x-3-4x}{2}= -1,5 \)



ПОЗЖЕ